Morality and Legality of Secession - Bossacoma Busquets, Pau. author. aut Link
XXI, 386 p. 2 illus.
Keywords: This book explores secession from three normative disciplines: political philosophy, international law and constitutional law. The author first develops a moral theory of secession based on a hypothetical multinational contract. Under this contract theory, injustices do not determine the existence of a right to secede, but the requirements to exercise it. The book’s second part then argues that international law is more inclined to accept and advance a remedial right approach to secession. Therefore, justice as multinational fairness is to be fully institutionalized under the constitutional law of liberal democracies. The final part proposes constitutionalizing a qualified right to secede with the aim of fostering recognition and accommodation of national pluralism as well as cooperation and compromise between majority and minority nations. Pau Bossacoma Busquets is Lecturer in Public Law at Pompeu Fabra University, Spain, and legal advisor of the Catalan Government. He is a member of the UPF Political Theory Research Group, the Evolution of Institutions Observatory and the Edinburgh Centre for Constitutional Law. He has authored several academic books, chapters and papers on constitutionalism, democracy, citizenship, nationalism, self-determination, sovereignty and territorial autonomy.